Analysing the linkage between total factor productivity and tourism growth in Latin American countries - Tzeremes, Panayiotis (Universidad ESAN. ESAN Ediciones, 2022)
Purpose: The study aims to investigate the nexus between total factor productivity and tourism growth in Latin American countries for time series data from 1995 to 2017. Design/methodology/approach: Using the extension of the Granger noncausality test in the nonlinear time-varying of Ajmi et al. (2015), the study points out the interconnectedness between the variables during the period. Findings: The study found nonlinear causality between the variables. Particularly, studying the conclusions for the time-varying Granger causality fashion, it can be noticed that the one-way causality from total factor productivity to tourism growth is obtained for Argentina, Bolivia, Brazil, Uruguay and Venezuela, while the vice versa is confirmed for Chile, Ecuador and Nicaragua. Lastly, the study dissected the plots of the curve causality. Practical implications: In view of the results, some crucial policy implications could be suggested, such as, under certain circumstances and as an exceptional case, the use of policy instruments such as targeted investment, marketing and the support of tourism organizations focused on driving a tourism-led-based productivity and/or tourism programs and projects. Originality/value: The current work is distinguished from the existing body of understanding in several substantial directions. This work explores, for the first time, the linkages between the total factor productivity index and tourism growth for Latin American countries. No single attempt has been known to investigate this interaction by using nonlinear causality, and this study determines the shape of the curve between the total factor productivity index and tourism growth for each country.

Propósito: El estudio tiene como objetivo investigar el nexo entre la productividad total de los factores y el crecimiento del turismo en los países de América Latina para datos de series temporales de 1995 a 2017. Diseño/metodología/enfoque: Utilizar la extensión de la prueba de no causalidad de Granger en la variación no lineal en el tiempo de Ajmi et al. (2015), el estudio señala la interconexión entre las variables durante el período. Hallazgos: El estudio encontró causalidad no lineal entre las variables. En particular, al estudiar las conclusiones para la moda de causalidad de Granger variable en el tiempo, se puede observar que la causalidad unidireccional de la productividad total de los factores al crecimiento del turismo se obtiene para Argentina, Bolivia, Brasil, Uruguay y Venezuela, mientras que se confirma lo contrario. para Chile, Ecuador y Nicaragua. Por último, el estudio diseccionó los gráficos de la curva de causalidad. Implicaciones prácticas: En vista de los resultados, se podrían sugerir algunas implicaciones políticas cruciales, como, en determinadas circunstancias y como caso excepcional, el uso de instrumentos políticos como la inversión selectiva, el marketing y el apoyo de organizaciones turísticas centradas en impulsar un productividad basada en el turismo y/o programas y proyectos turísticos. Originalidad/valor: El trabajo actual se distingue del conjunto de conocimientos existentes en varias direcciones sustanciales. Este trabajo explora, por primera vez, los vínculos entre el índice de productividad total de los factores y el crecimiento del turismo en los países latinoamericanos. No se ha conocido ningún intento de investigar esta interacción mediante el uso de causalidad no lineal, y este estudio determina la forma de la curva entre el índice de productividad total de los factores y el crecimiento del turismo para cada país.
Keywords: Total factor productivity; Tourism growth; Productividad total de los factores; Time-varying approach; Crecimiento del turismo; Enfoque variable en el tiempo; Latin American countries; Países de América Latina; https://purl.org/pe-repo/ocde/ford#5.02.04